2003
DOI: 10.1115/1.1555655
|View full text |Cite
|
Sign up to set email alerts
|

Surface Enhancement of Al2O3 Fiber With Nanosized Al2O3 Particles Using A Dry Mechanical Coating Process

Abstract: Currently, fabrication of composite materials is of great interest in industry. By combining materials of different properties, we can produce new composite materials with synergetic functionality that individual materials do not possess. In this study, Al2O3 nanosized particles were coated on Al2O3 fiber substrates using a dry mechanical coating technique employing high shear and compression forces. The materials thus synthesized had high surface area with good dispersion for enhanced reactivity and were stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Consisting of an elliptic rotor encased in an elliptical vessel, the dry particle coating system (Fig. 1) utilizes a dry coating technique to produce the powder composites [21][22][23][24][25] . The rotor operates at high revolution while the vessel rotates at low speeds in the opposite direction.…”
Section: Methodology Dr Y Particle Coating Systemmentioning
confidence: 99%
“…Consisting of an elliptic rotor encased in an elliptical vessel, the dry particle coating system (Fig. 1) utilizes a dry coating technique to produce the powder composites [21][22][23][24][25] . The rotor operates at high revolution while the vessel rotates at low speeds in the opposite direction.…”
Section: Methodology Dr Y Particle Coating Systemmentioning
confidence: 99%
“…Assuming the surface areas of the fiber and the nanoparticles are independent, the total surface area of the product can be considered as the sum of individuals (Coowanitwong et al, 2003a) as shown below:…”
Section: Set Iii: Effects Of Cuo and Al 2 O 3 Loadings And Temperaturementioning
confidence: 99%
“…This technique applies high shear and compression forces to adhere REMOVAL OF NITROGEN OXIDES BY DRY MECHANICAL COATING TECHNIQUE 139 guest materials onto a host substrate (Watano et al, 2000;Pfeffer et al, 2001). With intensive compression and shear forces, good dispersion and a high degree of mixing of the guest materials on the substrates can be achieved (Iwasaki et al, 2000;Coowanitwong et al, 2003a). The operation is simple (Iwasaki et al, 2002), and the process is economical and environmentally friendly by not producing organic or aqueous waste streams (Singh et al, 1997;Pfeffer et al, 2001).…”
Section: Introductionmentioning
confidence: 98%